Evaluación de la conservación de pulpas de parcha granadina (Agroindustria, Sociedad y Ambiente, 2022)
Passiflora quadrangularis L. known in Venezuela as: royal passion fruit, badea or granadina passion fruit belongs to the Passifloraceae family, it is the largest fruit of the passionflower family and one of the most appreciated for its delicate flavor and aroma. It is also attributed digestive and antiscorbutic properties, so its consumption provides health benefits. The objective of this work was to evaluate the stability, in storage at room temperature and refrigeration, of some physicochemical, nutritional and microbiological properties of passion fruit pulp formulations sweetened with sucrose using heating at 90°C, pH ( 3.53-4.3), water activity between (0.948-0.955) with the addition of ascorbic acid, citric acid, sodium benzoate and potassium sorbate as preservatives. Three (3) formulations were studied; F1: (Pulp + Ascorbic Ac. + Citric Ac.), F2: (Pulp + Ascorbic Ac. + potassium sorbate), F3: (Pulp + Ascorbic Ac. + sodium benzoate). The pulp formulations stored at room temperature (RT) of 28°C and refrigeration temperature (TR) of 5°C, were evaluated at 0, 10, 15 and 20 days. Physicochemical analyzes (pH, aw, °Brix, % Acidity, % Vitamin C, % Total Sugars.), microbiological analysis (mesophilic aerobes, molds and yeasts) were performed. In the microbiological results, a count below the minimum permissible limit of mesophilic aerobes, molds and yeasts, for human consumption, described in the COVENIN 2395-89 standard, was obtained. The conservation of the formulations of passion fruit pulp from Granada was stable physicochemically, microbiologically and using combined methods, and its commercial life was estimated for a time of 20 days. The thermal treatment and the combinations of additives selected for the elaboration of the product of passion fruit from Granada allow to maintain an appreciable content of vitamin C.
Keywords: Badea pulp; heat treatment; conservation; quality